Illusory Interior: Public Housing as Uncanny Site - Widyaevan, Dea Aulia (Interiority, 2023)
In 2021, Indonesia participated in the London Design Biennale, focusing on the theme of Resonance. The pavilion's response centred around public housing as an uncanny site, examining the psychological barriers faced by evicted communities during their transition to public housing. This study provides a conceptual analysis by exploring how the uncanny aspects of the occupants' experiences are expressed in installation using the illusory interior as a spatial metaphor. Through practice-led research, utilising ethnographic surrealism and narrative inquiries, data was gathered and translated into artistic mediums through various experiments. The study identifies several factors contributing to the uncanny sensation among public housing occupants, based on the occupants' experiences in public housing in Rancacili (Bandung) and Penjaringan (Jakarta), such as the shift from horizontal to vertical living, inadequate unit design, the absence of communal spaces, and a lack of ownership. The pavilion design attempts to integrate design theory and art practice, showcasing how installation art can express interiority within built spaces and extend it into installation art. Here, the uncanny acts as a methodological framework for critiquing space and transforming interiority into tangible forms by interpreting the actual conditions using installation art as a medium.